The practice of social research - Babbie, Earl R. (Boston, MA : Cengage, 2021)
Packed with hands-on applications, Babbie's THE PRACTICE OF SOCIAL RESEARCH, 15th Edition, equips your students with the tools they need to practically apply research concepts as both researchers and consumers. Known as the'gold standard' for research methods, the text delivers a comprehensive, straightforward introduction to the field of research as practiced by social scientists. Dr. Babbie emphasizes the research process by showing students how to design and construct projects, introducing the various observation modes in use today. The new edition includes'What do you think?' puzzles that immediately draw students into chapter concepts. General Social Survey data is updated throughout while new coverage includes the global use of social research, the emerging role of big data, demographic analysis and more.-publisher's description.
Includes bibliographical references (pages 540-554) and index.
Keywords: Social sciences -- Research; Social sciences -- Methodology